Unilateral Optic Disc Pseudo-duplication with Contralateral Chorioretinal Coloboma: A Case Report - Feizi, Mohadeseh (Journal of Ophthalmic and Optometric Sciences, 2025)
Optic disc pseudo-duplication (ODPD) is a rare condition presumed to be a form of retinal coloboma. In this report, we present the case of a child with ODPD in one eye and diffuse chorioretinal coloboma, along with microcornea in the fellow eye. This case supports the hypothesis that ODPD may be linked to the colobomatous nature of the condition.